Pengaruh metode latihan dan kapasitas vital paru terhadap vo2max pada atlet futsal pelajar - Christanto Sepang, Onan; Budi Raharjo, Bambang; Sulaiman, Sulaiman; Sumartiningsih, Sri (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
This study investigates the effect of extensive, intensive interval training methods and the vital lung capacity of futsal athlete students to improve the vo2max. This type of research was quasi-experimental with a 2x2 factorial design. 24 male student futsal athletes, age 15.95±0.55, height 164.61±6.90, and weight 53.23±8.11, met the inclusion criteria, signed informed consent and participated in this study. The interventions were extensive interval training methods for running on a 20-meter track and intensive interval training for running on a 100-meter track. Treatment is done 16 times, three times a week, and progressive sets, repetitions, time, and rest. Vo2max was measured with a multistage fitness test, and lung vital capacity was measured with spirometry SP70B. Data analysis used two-way ANOVA, the data was tested for normality and homogeneity. The study showed that extensive pretest 37,53±1,37 and posttest 50,68±1,00 (p=0.05), and intensive pretest 37,04±1,45 and posttest 49,18±1,37 (p=0.05) interval training improves VO2Max, repestivully. There is no interaction between extensive and intensive training methods on lung vital capacity. The study concludes that extensive and intensive training methods are useful to improve the vo2max of students' futsal athletes. The extensive interval training method is more effective in improving vo2max.